FENG SHUI IN MODERN HOUSE DESIGN SEARCHING FOR THE RATIONALE AND POSSIBLE IMPACTS ASSESSMENT - Linda, OCTAVIA; Tanuwidjaja, GUNAWAN (DIMENSI (Journal of Architecture and Built Environment), 2014)
The Feng Shui, the "wind-water", is a Chinese system of geomancy using the laws of both Heaven and Earth for harmony and balance of life with the positive qi. Feng Shui is widely used to orient temples, palaces, shops, houses, and other structures, with the reference to local features such as bodies of water, stars, or a compass. The Feng Shui also informs the physical arrangements for manipulation and channeling the qi (positive or negative energy). Although Feng Shui is related to traditional believe and propitious manner, but some of its principles are rational. The current research is conducted to investigate any positive impacts of the Feng Shui application in modern house design. A house in Jakarta designed with Feng Shui was analyzed. The strategies were later examined based on the sustainable architectural design principles, especially its impact on the house functionality.